Applying Jewish Wisdom to Philanthropy: The Case of Aggripas and the Sages. Issue 4 (2nd October 2019) - Kaunfer, Elie
ABSTRACT: This article attempts to test the hypothesis that Jewish wisdom can impact the real-life work challenges of non-profit/philanthropy power dynamics. By examining the narratives of King Aggripas and the sages, I explore an analogue to these power dynamics in rabbinic literature. In M Sotah 7:8, the rabbis flatter Aggripas by calling him their brother, even though he is not. The later rabbinic examinations of this interaction offer multiple ways of understanding this encounter, all relevant to modern-day applications. In addition, other stories of Aggripas reported in rabbinic literature further nuance this exploration.